Analisis Kinerja Pengelolaan Anggaran Pendapatan Dan Belanja Daerah Pemerintah Daerah Kabupaten Sarolangun - Noraiyan, Noraiyan (Jurnal Dinamika Manajemen, 2017)
This research aims to analyze the level of development of the Regional Revenue and Expenditure Budget and to analyze the performance of the management of the revenue budget in the local government of the Sarolangun Regency in terms of the routine expenditure ratio and to analyze the ability of the budget and financing of the Sarolangun Regency Government. The research method used is a descriptive analysis method of collecting quantitative data. The results of this study indicate that the level of development of the Regional Revenue and Expenditure Budget for Sarolangun Regency during the period 2003-2012 experienced an average development of 18.16% with the Routine Expenditure Ratio of Sarolangun Regency during the period 2003-2012 occurring effectively and efficiently every year where the average -The average regional routine expenditure ratio is 0.73 per year. Meanwhile, seen from the ratio of Regional Development Expenditure in Sarolangun Regency during the period 2003 - 2012 the average was 0.52 per year. This shows that the Regional Financial Performance of the Sarolangun Regency Government occurred effectively and efficiently in accordance with the target and the Ratio of Budget Effectiveness of Regional Income and Expenditures of Sarolangun Regency during the 2003 – 2012 Period was very effective and efficient where the use of APBD Realization and APBD Targets was in accordance with the budget so that it was even. -the average APBD Effectiveness Ratio reaches a value of 0.90. This means that the point of balancing financial performance and the effectiveness of the Sarolangun Regency APBD is effective.